Information, Knowledge and Agile Creativity - Goria, Stéphane; Humbert, Pierre; Roussel, Benoît (Wiley-ISTE, 2019)
Information, Knowledge and Agile Creativity will enlighten entrepreneurs, and is ideal for facilitating an organization's ability to react and adapt to its environment. Creativity is a system that engenders innovation. While integral at the conception stage, it is also important before and after this phase. This book offers a collection of tools, as well as a methodology, to estimate the agility of an organization to generate and transform ideas into solutions that are not only new but also adapted to their users. To this end, this book presents strategic foresight and problem comprehension methods; tools of sharing and visual information formatting; animation tips for creativity workshops; techniques for generating ideas; and tools for visualizing and mapping ideas, information, and knowledge.
Online resource; Title from title page (viewed December 12, 2019)